Purification of a recombinant baculovirus of Autographa californica M nucleopolyhedrovirus by ion exchange membrane chromatography - Grein, Tanja A.; Michalsky, Ronald; López, Maria Vega; Czermak, Peter (My University, 2012)
Significant progress in the application of viral vectors for gene delivery into mammalian cells and the use of viruses as biopesticides requires downstream processing that can satisfy application-specific demands on performance. In the present work the stability and ion exchange membrane chromatography of a recombinant of Autographa californica M nucleopolyhedrovirus is studied. To adjust the degree of purification the effect of ionic conductivity or pH on the viral infectivity was assessed (0.77-78.00 mS/cm, pH 3-8). Infectivity decreased rapidly by several orders of magnitude at below 5 mS/cm (i.e., 0.49 MPa osmotic pressure change) or at below pH 5.5 (rationalized with particle aggregation). The virus was concentrated and purified via adsorption (0.2-1.1 x 10[superscript]16 pfu/m[superscript]3 chromatographic bed volume, 0.6-1.1 x 10[superscript]12 pfu/m[superscript]2 membrane area facing the incident fluid flow) and elution at pH 6.1 and 6.35 mS/cm from three strong anion exchange membranes. Virus recovery and concentration in accord with the volume reduction were obtained using a polyether sulfone-based membrane with quaternary ammonium ligands. The level of host cell protein (down to below the detection limit) and suspended DNA (below 93 pg DNA per 106 pfu) are reported for each membrane employed, for the purpose of comparability, under equal adsorption or elution conditions respectively.
Keywords: Gene therapy; Pesticide; Baculovirus; Ion exchange membrane chromatography; Conductivity; pH